-6(2x+3)=-(5x-10)

Simple and best practice solution for -6(2x+3)=-(5x-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(2x+3)=-(5x-10) equation:



-6(2x+3)=-(5x-10)
We move all terms to the left:
-6(2x+3)-(-(5x-10))=0
We multiply parentheses
-12x-(-(5x-10))-18=0
We calculate terms in parentheses: -(-(5x-10)), so:
-(5x-10)
We get rid of parentheses
-5x+10
Back to the equation:
-(-5x+10)
We get rid of parentheses
-12x+5x-10-18=0
We add all the numbers together, and all the variables
-7x-28=0
We move all terms containing x to the left, all other terms to the right
-7x=28
x=28/-7
x=-4

See similar equations:

| (6.1)+t=5.4 | | 7b-20=3b+20 | | (X^2)(2^x)-64(2^x)=0 | | 4x-3/2=-4 | | 4^1-2x=3^2x-5 | | (-3.48)+e=6.21 | | 4x-30=10x | | X^x=64 | | 5(x+2)^2=180 | | -20=4u-8 | | 2.7x-66=1.1x+6 | | 9(x+4)=1-2x | | 5y-17y=6 | | 3-3r=-3 | | -24x=-24x+-111 | | 7x-4=4x+19 | | 8x+7(2+3x)=-6(2x+5) | | 7x-14=4x+9 | | 2.5-0.02x=-0.3 | | F=22c+32 | | 24/b+7=-5 | | 8(y-4)=5y-2 | | 3(2x+1)x=−8 | | 8a-4-4a=2+6a | | 14-9x=-80=-8x | | 5000=2x^2+200x | | -3(k+5=15 | | 24=-16(m+1)+18 | | -9-m=1+2m-1 | | 0=16t2+66t+2 | | 10+n=2n+6 | | 0,8x=31550 |

Equations solver categories